Students' Value Orientations in Contemporary China: Analysis of Measurement Invariance and Latent Mean Differences in Comparison With Students From Germany and Russia. (May 2017) - Heim, E.; Scholten, S.; Maercker, A.; Xiu, D.; Cai, D.; Gao, Z. H.; Lu, S.; Sang, Z. Q.; Wei, J.; Kochetkov, Y.; Margraf, J.
The present study examined Chinese students' personal value orientations according to the Schwartz value theory in comparison with students from Germany and Russia. The theory postulates 10 value orientations grouped into four higher-order factors: conservation versus openness to change and self-transcendence versus self-enhancement. Schwartz' value orientations have been extensively investigated in Europe but less in East Asian countries such as China. We hypothesized that Chinese students would score higher on conservation and self-enhancement than German and Russian students, but lower on self-transcendence. Regarding openness to change, a null hypothesis was formulated. Students from China ( n = 9, 601), Germany ( n = 1, 118), and Russia ( n = 3, 890) completed the Portrait Values Questionnaire (PVQ-21). To ensure methodological preconditions for cross-cultural comparison, measurement invariance of the PVQ-21 was tested. In a first step, confirmatory Factor Analysis (CFA) was conducted separately for each country. Due to the high correlation between the 10 values, the four higher-order dimensions were studied separately. Configural, metric, and scalar invariance models were tested using multigroup CFA. Full metric and partial scalar invariance models held for all higher-order factors. Thereafter, latent means of values were compared across samples. As a result, Chinese students scored highest on the four higher-order dimensions when compared with Russian and German samples, thus the hypotheses were only partly confirmed. Results of this study could reflect the value conflicts emerging from various cultural influences in contemporary China: Young people are confronted with daily negotiation between Confucian tradition and the rapid economic development.